IMPLEMENTASI KNOWLEDGE MANAGEMENT DALAM KEMENKEU CORPORATE UNIVERSITY - Agus Suharsono; Ariefina Sri Indaryani (LPPM Universitas Pamulang, 2020)
Learning from the Ministry of Finance Corporate University utilizes the Ministry of Finance Learning Center as a Knowledge Management. This paper wants to know and analyze how Knowledge Management is implemented in the Ministry of Finance Learning Center. The method used is qualitative with inductive logic analysis. The results of the study indicate that it is implemented using the internet. The formation of knowledge sharing habits has been implemented, but there are still many learning videos with few viewers, it should be made based on the eyes of the training in the Pusdiklat or subjects in PKN STAN. The making of learning videos is still dominated by Widyaiswara, officials or employees of the Directorate General of Taxes as very little Group Owner Skills, so rules need to be made that require officials or employees of the Directorate General of Tax to make learning videos based on best practice and tacit knowledge. Knowledge Management regulation umbrella is the Regulation of the Head of the Financial Education and Training Agency and Minister of Finance Regulation. The Knowledge Management strategy in the Ministry of Finance Learning Center is aligned with the Ministry of Finance's change management strategy because it is one of the central themes of the strategic initiative of the Ministry of Finance's bureaucratic reform program and institutional transformation.Keywords: Corporate University, Knowledge Management, Skill Group Owner.Abstrak